TANGGUNG JAWAB PELAKU USAHA WANPRESTASI DALAM TRANSAKSI E-COMMERCE - Noverwin Saragih, Frans; Wita, I Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 02, Februari 2013, 2013)
E-Commerce is an engagement that connects the parties to carry out a commercial activity over the Internet. What distinguishes e-commerce with conventional transactions are the parties involved in these activities are not directly face to face, so the potential event of wanprestatie is greater than with conventional transactions. This paper describes how the responsibilities of businesses against the wanprestatie to consumer that business are in wanprestatie.
Keywords: Wanprestatie, E-Commerce, Responsibility